Elastoplastic behavior of welded connections in square section steel pipes submitted to monotonic load (Gaceta Técnica, 2019)
This research aims to analyze the elastoplastic behavior of welded connections of square section steel tubes subjected to monotonic loading, by means of the theoretical - experimental comparative analysis of the distortion of the cross section geometry of the elements of the beam - column joint. For the experimental tests it was necessary to build a rigid support frame designed with STAAD software. Pro v8i, of fixing and assembly to the gantries and load application system of the universal machine of the Materials Laboratory of the Faculty of Engineering of the University of Zulia. In every test a progressive load (monotonic load) was applied on the upper connection of the gantry to systematically to measure displacements and distortion of the geometry of the beam jointing elements column of the lower connection. While the theoretical model was performed using the finite element program [4] ANSYS Workbench. The obtained results show that: the welded connection presents a local failure by punching in the column that reduces the theoretical plastic moment capacity of the gantry "Mp" by 46%, scenario of concern for being this capacity used in the design under the theory Design for Load and Resistance Factors (LRFD). The welded connection (node) does not meet the weak beam strong column criterion established by Norma. The column of the welded joint must be reinforced to avoid the formation of the plastic ball joint and a possible mechanism of collapse in the gantry
Keywords: monotonic charge; distortion of geometry; ANSYS Workbench